2020
DOI: 10.3390/toxins12100610
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Deoxynivalenol Has Different Impacts on Intestinal Barrier and Stem Cells by Its Route of Exposure

Abstract: The different effects of deoxynivalenol (DON) on intestinal barrier and stem cells by its route of exposure remain less known. We explored the toxic effects of DON on intestinal barrier functions and stem cells after DON microinjection (luminal exposure) or addition to a culture medium (basolateral exposure) using three-dimensional mouse intestinal organoids (enteroids). The influx test using fluorescein-labeled dextran showed that basolateral DON exposure (1 micromolar (µM) disrupted intestinal barrier functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Basolateral DON exposition caused inhibited intestinal stem cell activity through the Wnt/β-catenin pathway [196]. Based on this study, Hikaru Hanyu et al decided to go one step further, demonstrating that basolateral exposure was more toxic than luminal DON exposure in terms of intestinal barrier functions and stem cells [197]. It is worth mentioning that DON toxicity observed in vitro and in vivo might be different, possibly due to biological barrier function.…”
Section: Deoxynivalenolmentioning
confidence: 83%
“…Basolateral DON exposition caused inhibited intestinal stem cell activity through the Wnt/β-catenin pathway [196]. Based on this study, Hikaru Hanyu et al decided to go one step further, demonstrating that basolateral exposure was more toxic than luminal DON exposure in terms of intestinal barrier functions and stem cells [197]. It is worth mentioning that DON toxicity observed in vitro and in vivo might be different, possibly due to biological barrier function.…”
Section: Deoxynivalenolmentioning
confidence: 83%
“…Altered intestinal epithelial structure may impact the route and extent of absorption or passage through the intestinal lineage of exogenous as well as endogenous chemicals (74). A recent in vitro study also suggested basolateral exposure to low concentrations of DON to disrupt epithelial tight junction proteins and further barrier functionality of enteroids (103). This highlights the importance of investigations on cellular uptake and efflux of foodborne substances.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a ketone group at position C8 is characteristic of B trichothecenes. Deoxynivalenol also contains an epoxide group which enables the mycotoxin to bind to a large number of eukaryotic ribosome subunits and disrupt the activity of peptide transferase, thus compromising the elongation or shortening of peptide chains ( 7 ). Deoxynivalenol affects the cellular transport rate and enzyme metabolism in the cytoplasm ( 8 ), it leads to changes in affinity for active binding sites and disrupts protein synthesis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%